Theater and Spectacle in the Art of the Roman Empire - Dunbabin, Katherine M. D. (Book collections on Project MUSE., 2016)
Theater, spectacle, and performance played significant roles in the political and social structure of the Roman Empire, which was diverse in population and language. A wide and varied range of entertainment was available to a Roman audience: the traditional festivals with their athletic contests and dramatic performances, pantomime and mime, the chariot races of the circus, and the gladiatorial shows and wild beast hunts of the arena. In Theater and Spectacle in the Art of the Roman Empire, which is richly illustrated in color throughout, Katherine M.D. Dunbabin emphasizes the visual evidenc.